Digital Mandates and Their Management: Strategies for Usage of Social Media by Brazilian Federal Legislators. Issue 4 (6th September 2021) - de Barros, Antonio Teixeira; Bernardes, Cristiane Brum; de Faria, Cristiano Ferri Soares; Busanello, Elisabete
Abstract: The study aims to analyse the strategies adopted by the Brazilian Federal Chamber of Deputies during the period 2019–2022 (56th legislature) on social media platforms. The survey with political advisers includes the following platforms: Facebook, Instagram, YouTube, Twitter, WhatsApp, Telegram and LinkedIn. The sample consists of 155 informants, 30.21% of the total of 513 parliamentary offices. The conclusions show that 65% of the offices adopt specific strategies for each type of social media, although there is a wider principle, which is the constitution of multi-networks, in a coordinated and complementary way. Within these strategies, the disclosure regarding the parliamentarian's own actions and the agenda of their electoral bases is prioritized over institutional legislative activities.